Analysis of Exchange Rate Pass Through with Asymmetric Causality Tests in Turkey - Bayat, Tayfur; Ozcan, Burcu; Tas, Sebnem (Eskisehir Osmangazi Univ, Fac Education, 2015)
In this study, we focused on the relationship between structural breaks and causality in order to reveal the exchange rate pass-through effect over the period January 2003 to December 2013 in Turkey. The traditional univariate unit root tests such as Dickey-Fuller (1979) test, Phillips-Perron (1988) test, and Zivot-Andrews (1992) test with one endonegous break were employed. Finally, the linear Granger causality test derived from the vector autoregressive model and the causality test developed by Breitung and Candelon (2006) were used. The results indicated that there is a structural break corresponds to the December 2007. According to the results of empirical analysis, the implementation of floating exchange rate policy along with the inflation targeting strategy has led the stability of exchange rates. Therefore, it was concluded that there is no pass-through effect in the economy of Turkey.
Keywords: Exchange Rate Pass-Through Effect; Unit Root Tests; Causality in the Frequency Domain; Asymmetric Causality